Recycling Face Mask Fibers in Geopolymer-Based Matrices for Sustainable Building Materials - Roberto Ercoli; Paola Stabile; Elena Ossoli; Irene Luconi; Alberto Renzulli; Eleonora Paris (Ceramics)
This study investigates the upcycling of disposable face masks, which were produced in vast quantities during the COVID-19 pandemic and are now widely stockpiled in public institutions, destined for landfills after reaching expiration dates. The research focuses on incorporating shredded mask fibers into geopolymer matrices, evaluating the effects on mechanical and thermal properties to develop sustainable, high-performance materials. This approach addresses critical environmental, social, and economic challenges by transforming problematic waste into valuable resources while promoting sustainable building practices, such as developing insulating products for the construction industry. Mechanical testing demonstrated that adding shredded mask fibers (2 mm and 6 mm in size, up to 5 wt.%) enhanced the flexural strength of geopolymeric products. The optimal performance was achieved by adding 3 wt.% of 2 mm-length fibers, resulting in a flexural strength of 4.56 ± 0.23 MPa. Regarding compressive strength, the highest value (54.78 ± 2.08 MPa) was recorded in geopolymers containing 1 wt.% of 2 mm fibers. Thermal insulation properties of the materials improved with higher mask content, as evidenced by reductions in thermal conductivity, diffusivity, and specific heat. The lowest thermal conductivity values were observed in geopolymers containing 5 wt.% (0.4346 ± 0.0043 W·m−1·K−1) and 3 wt.% (0.6514 ± 0.0002 W·m−1·K−1) of 2 mm mask fibers. To further enhance thermal insulation, geopolymers with 5 wt.% mask fibers were foamed using H2O2 to obtain highly porous light materials, obtaining a reduction of thermal conductivity (0.3456 and 0.3710 ± 0.0007 W·m−1·K−1). This research highlights the potential of integrating fibrous waste materials into advanced construction technologies, offering solutions for waste reduction and development in the building sector toward sustainability.